Advanced vertebral tuberculosis in an adolescent - Enri Rodríguez Montero; Gerardo Téllez Gamayo; Fátima Flores Bolivar (Centro Provincial de Información de Ciencias Médicas, 2020)
The case report of an 18 years patient, HIV seropositive is described. He was assisted at Luena Provincial Hospital, angolan province of Moxico due to a lumbar pain. A computerized axial tomography was carried out, which showed great vertebral destruction and bilateral paravertebral collections. The patient maintained an unfavorable clinical course and died 20 days after the diagnosis.